THE USE OF POLARIZED LIGHT IN THE ANALYSIS OF METALS AND ALLOYS - A. G. Anisovich (Литьë и металлургия)
Application of polarized light in the metallographic annalysis of metals and alloys is considered, its application for the analysis of ninmetallic inclusions is shown. examples of application of differential and interferential contrast for the annalysis of structure of metals in reflected light are shown.